Evaluation of new pasture legumes options in the Pampa-Patagonia transitional region of Argentina - Renzi Pugni, Juan Pablo; Chantre Balacca, Guillermo Ruben; Reinoso, Omar Juan; Quintana, Matias; Grand, Andres Carlos; Cantamutto, Miguel Angel (Ediciones INTA, 2022)
Biodiversity in forage legumes adapted to semiarid-arid conditions is scarce. In the Pampa-Patagonia transitional region of Argentina (PTRA), the annual rainfall is 440 mm with annual evapotranspiration of 1690 mm. Only Vicia villosa Roth shows agronomic adaptation to such an environment. Dry matter production of 19 selected legume species was compared to V. villosa (cv. Patagonia INTA) in the first year of establishment during 2015-to-2019. Medicago truncatula Gaertn. and Trifolium subterraneum L. (cv. Goulburn) showed high winter dry matter production, similar to V. villosa, but poor biomass production in spring. Spring dry matter contributed ≈ 80% of the total biomass per year. Preliminary results showed that Onobrychis viciifolia Scop. overcame the rest of the accessions evaluated, except for V. villosa. O. viciifolia could be considered a complementary species to V. villosa, a candidate for initiating a process of breeding as a new pasture legume for semiarid-arid environments. This is the first record of the potential use as a pasture of O. viciifolia in the PTRA.